Ammonite [videorecording (DVD)] - Lee, Francis, 1968 or 1969-; Winslet, Kate; Ronan, Saoirse, 1994-; Jones, Gemma; McArdle, James, 1989- (Universal Pictures Home Entertainment, 2021)
In the 1840s, acclaimed self-taught palaeontologist Mary Anning works alone on the wild English coastline. She hunts for common fossils to sell to rich tourists to support herself. When one such tourist arrives in Lyme, he entrusts Mary with the care of his young wife Charlotte, who is recuperating from a personal tragedy. Despite their differences, it is the beginning of a passionate and all-consuming love affair that will defy all social bounds and alter the course of both lives irrevocably.